Penguatan Kapasitas Komunitas Pasar Kita Menuju Ekonomi Inklusif Berkonsep Syari’ah Di Desa Moderasi Beragama Kabupaten Jember - Ningrum, Nurita Kustiari (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2025)
Indonesia's economic growth experienced a slowdown of 4.9 percent. In the MSME sector, women's empowerment is essential. MSME products must be designed according to export standards for product expansion, creativity, and innovation. Pasar Kita is a community of women's MSMEs across cultures and religions. Our market consists of the leading market and sub-district markets. The prominent market members are all independent women, women with broken homes and victims of domestic violence cases. Implementing the Sharia concept is a strategic and progressive step. Combining local wisdom, religious values ​​and business principles with sharia creates inclusive economic opportunities, strengthens cultural diversity, and promotes peace and social harmony in the regional and global realms. The service approach uses ABCD (Asset-Based Community Development). The result of strengthening the capacity of our market community towards an inclusive economy with a Sharia concept in the religiously moderate village of Jember Regency is that the community has the abilities obtained, namely Developing Skills and Critical Understanding. Our Market Community has Technical Capabilities in managing marketing strategies. They also have a sustainable understanding of Sharia Economic Principles, Financial Management Skills, Ethical Digital Marketing and Sustainable Product Management.